2008
DOI: 10.1007/s00280-007-0660-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of topoisomerases and RNA transcription in the action of the antitumour benzonaphthyridine derivative SN 28049

Abstract: Purpose-SN 28049 (N-[2-(dimethylamino)ethyl]-2,6-dimethyl-1-oxo-1,2-dihydrobenzo[b]-1,6-naphthyridine-4-carboxamide) is a DNA intercalating drug that binds selectively to GC-rich DNA and shows curative activity against the Colon 38 adenocarcinoma in mice. We wished to investigate the roles of topoisomerase (topo) I, topo II and RNA transcription in the action of SN 28049.Methods-We used clonogenic assays to study the cytotoxicity of SN 28049; RNA interference and enzyme assays to examine the role of topo I in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…SN 28049 is a DNA binding drug whose dominant action has been shown to be as a poison of topoisomerase IIα [12]. Its effects on NZM3 cells are similar to that of the clinical drug doxorubicin, and in fact SN 28049 has similar potency to this drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SN 28049 is a DNA binding drug whose dominant action has been shown to be as a poison of topoisomerase IIα [12]. Its effects on NZM3 cells are similar to that of the clinical drug doxorubicin, and in fact SN 28049 has similar potency to this drug.…”
Section: Discussionmentioning
confidence: 99%
“…The action of SN 28049 was studied in HTETOP human fibrosarcoma cells in which topoisomerase IIα could be down-regulated by addition of tetracycline. SN 28049 induced a 99% reduction of viability in HTETOP wildtype cells but only a 40% reduction when topoisomerase IIα was down-regulated [12], strongly suggesting that topoisomerase IIα is its major enzyme target. Moreover, Jurkat leukaemia cell lines that have developed resistance to doxorubicin or amsacrine [13] have a much reduced topoisomerase II content (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…43) Aclarubicin showed the highest ERs and DERs against all of the tumors examined among topoisomerase inhibitors, and these activities are comparable to those of TAS-103 at 5 mg/ml (Tables 3, 4). It is interesting to note that aclarubicin is seemed to be a topo I and topo II inhibitor, 44) like TAS-103. 1) A clinical phase I study of TAS-103 has been carried out against 32 patients; including 16 colorectal, 7 lung, and 5 head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…[49] Nevertheless, the series exhibited much less dose potency against H460 cells than clinically 50 values against this line in the low nanomolar range. [58,59] Activity of Pyranonaphthoquinone Derivatives against the Catalytic Activity of Human IDO in LLTC-IDO Cells Next we examined the series' ability to inhibit the catalytic activity of IDO-1 in a cellular context by determining the extent to which each compound inhibited the production of the L-tryptophan catabolite, L-kynurenine, in the human IDO-1 overexpressing LLTC-IDO cells. The results showed that there was a dose dependent decrease in L-kynurenine production in the drug treated cells; however the potency of the effect was highly compound dependent (Fig.…”
Section: Resultsmentioning
confidence: 99%